Gunshot-related nerve injuries of the upper extremities: clinical, electromyographic, and ultrasound features in 22 patients - Shields, Lisa B. E.; Iyer, Vasudeva G.; Zhang, Yi Ping; Shields, Christopher B. (Frontiers in Neurology, 2024)
Objectives: Gunshot wounds of the upper extremities may cause permanent neurovascular injuries, leading to significant morbidity, chronic pain, functional loss, and disability. While there are many reports on the incidence and intraoperative findings in gunshot-related nerve injuries (GSNI) sustained during wars, there is a paucity of details pertaining to GSNI of the upper extremities in civilians. The goal of this paper is to provide the clinical, electrodiagnostic (EDX), and ultrasound (US) findings in 22 patients with GSNI of the upper extremities. Methods: This is a retrospective study of patients referred for EDX studies to evaluate the presence of nerve injury after sustaining GSWs to the upper extremities. All patients underwent EDX studies, and 16 patients had US evaluations. Numerous metrics were documented including presenting symptoms, neurological abnormalities, EDX findings, and US features. Results: The forearm was the most frequent location injury (8 [36%] patients). The ulnar nerve was the most common injured nerve (10 [45%] patients), followed by the brachial plexus (7 [32%] patients). All patients complained of muscle weakness; the most frequently affected muscles were the first dorsal interosseous (FDI) (14 [64%] patients) and abductor pollicis brevis (APB) (11 [50%) patients). Muscle atrophy was noted in 19 (86%) patients, 15 of whom had atrophy of the FDI. Axonotmesis was the type of nerve injury in all patients based on EDX studies. Of the 16 patients who underwent US studies, a neuroma in continuity was noted in 4 (25%) patients and neurotmesis in 1 (6.2%) patient. Eleven (69%) patients had enlarged and/or hypoechoic nerves. Conclusions: Axonotmesis of the ulnar nerve was the most common finding among patients sustaining gunshot injuries to the upper extremities. EDX and US studies provide valuable insight into the underlying pathophysiology and guidance for management of patients with GSNI of the upper extremities.